Ethical tensions in research: The influence of metatheoretical orientation on research ethics. Issue 1 (27th December 2016) - Barriage, Sarah; Buente, Wayne; Greifeneder, Elke; Greyson, Devon; Kitzie, Vanessa; Morales, Miraida; Todd, Ross
ABSTRACT: When developing one's own research agenda, early and mid‐career researchers continually negotiate how best to meet ethical standards and resolve ethical constraints using methodologically sound approaches. Often such struggles occur behind closed doors, their outcomes reflected in the institutional language of an ethical review board. This panel seeks to bring these struggles to the forefront by having panelists who study various populations discuss how they approach ethical challenges in their research. Due to the nature of the groups these panelists study, the panel provides a context where the site of ethical struggles, challenges, and tensions are exacerbated. Key issues to be discussed are: informed consent, risks to participants, and research design and dissemination. Discussion of these issues will be oriented around each participant's metatheoretical orientation to research in library and information science (LIS). Adopting such an approach will highlight some of the main challenges when engaging in ethical practices that may not align with institutional standards, as well as denote possible strategies for addressing them.